Metabolic, transcriptomic, and genetic analyses of candidate genes for seed size in watermelon - Wang, Xiqing; Yan, Wen; Real, Núria; Jia, Yunhe; Fu, Yongkai; Zhang, Xuejun; You, Haibo; Cai, Yi; Liu, Bin (Frontiers in Plant Science, 2024)
Seed size (SS) constitutes a pivotal trait in watermelon breeding. In this study, we present findings from an examination of two watermelon accessions, named BW85 and F211. Seeds from BW85 exhibited a significant enlargement compared to those of F211 at 13 days after pollination (DAP), with the maximal disparity in seed length and width manifesting at 17 DAP. A comprehensive study involving both metabolic and transcriptomic analysis indicated a significant enrichment of the ubiquinone and other terpenoid-quinone biosynthesis KEGG pathways. To detect the genetic region governing seed size, a BSA-seq analysis was conducted utilizing the F 2 (BW85 × F211) population, which resulted in the identification of two adjacent QTLs, named SS6.1 and SS6.2, located on chromosomes 6. SS6.1 spanned from Chr06:4847169 to Chr06:5163486, encompassing 33 genes, while SS6.2 ranged from Chr06:5379337 to Chr06:5419136, which included only one gene. Among these genes, 11 exhibited significant differential expression between BW85 and F211 according to transcriptomic analysis. Notably, three genes (Cla97C06G113960, Cla97C06G114180, and Cla97C06G114000) presented differential expression at both 13 and 17 DAP. Through annotation, Cla97C06G113960 was identified as a Ubiquitin-Conjugating Enzyme E2, playing a role in the ubiquitin pathway that mediates seed size control. Taken together, our results provide a novel candidate gene influencing seed size in watermelon, shedding light on the mechanism underlying seed development.